2016
DOI: 10.1136/annrheumdis-2016-eular.3473
|View full text |Cite
|
Sign up to set email alerts
|

THU0137 Non-Adherence To Subcutaneous Biological Therapy in Patients with Rheumatoid Arthritis. Arco Study

Abstract: BackgroundLack of adherence to medication in rheumatoid arthritis (RA) can worsen disease activity, but data on adherence to biological drugs is scarce.ObjectivesTo evaluate RA patients adherence to the subcutaneous (SC) biological treatment prescribed by the physician during the first year of treatment.MethodsRetrospective study in RA patients ≥18 years-old from 42 Spanish hospitals, which had been prescribed a SC biological drug 12 to 18 months prior to the study visit. Data were collected from patients' cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
3
20
1
Order By: Relevance
“…Adherence is reported to be lower with subcutaneous bDMARDs and more frequent dosing schedule. 28 29 Despite this, we did not find a difference in effectiveness when comparing TCZ-SC with TCZ-IV. Finally, we do not have data outside of the bDMARDs courses and thus could not explore other aspects as for example the rate of biologic-free remission between groups.…”
Section: Discussioncontrasting
confidence: 56%
“…Adherence is reported to be lower with subcutaneous bDMARDs and more frequent dosing schedule. 28 29 Despite this, we did not find a difference in effectiveness when comparing TCZ-SC with TCZ-IV. Finally, we do not have data outside of the bDMARDs courses and thus could not explore other aspects as for example the rate of biologic-free remission between groups.…”
Section: Discussioncontrasting
confidence: 56%
“…Another factor that is associated with persistence is the administration frequency: Patients using the monthly administration period had better adherence than those using more frequent dosing schedules [39]. …”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is the sustained clinical efficacy and safety observed in the long-term extension of clinical trials 1315,45. Another reason may be the monthly administration frequency;55 this point was also reflected by a retrospective multicenter observational study conducted in Spain, in which it was found that adherence was higher with a monthly administration of SC biologics compared with fortnightly or weekly administration 56. In addition, a study in axial SpA found that combination therapy of TNFis and DMARDs affects drug retention,57 while a study in RA identified the reason for persistence with biologics in RA to be multifactorial, including age, comorbidities, and patient type 58.…”
Section: Discussionmentioning
confidence: 99%